John T. Edge, Elizabeth Engelhardt & Ted Ownby (eds.), The Larder: Food Studies Methods from the American South, Athens: The University of Georgia Press, 2013. - Castilho, Maria Teresa (Cadernos de Literatura Comparada, 2017)
.